Economic impact of peste des petits ruminants outbreak and vaccination cost in northwest Ethiopia - Jemberu, Wudu T.; Knight-Jones, Theodore J.D.; Gebru, A.; Mekonnen, S.A.; Yirga, A.; Sibhatu, D.; Rushton, J. (International Livestock Research Institute, 2022)
This study was conducted to assess the economic impact and costs of PPR vaccination in Metema district, northwest Ethiopia. The economic impact of the disease was estimated from outbreak investigation and interviews of 233 smallholder farmers in PPR affected sub-districts. The cost of PPR vaccination was obtained from vaccination programs in six sub-districts and from secondary data from the district veterinary office. In investigated PPR outbreak, animal level PPR morbidity and mortality were, respectively, 50.7% and 21.6% in sheep and 51.3% and 25.1% in goats. In the sub-district 82.7% of sheep flocks and 87% of goat flocks had PPR. The mean flock level loss for affected sheep flocks was USD 329 (95%CI: 250 -408) and USD 300 (95%CI: 247-353) for affected goat flocks. The losses in all study flocks (including those without cases) during the outbreak equated to USD13.4 per sheep and USD12.9 per goat. Mortality accounted for more than 70 % of the total losses in both sheep and goat flocks. Vaccination costs for PPR was estimated at USD 0.13 per correctly vaccinated animal, with delivering the vaccine to the animal accounting for 44% of vaccination costs. Based on the estimated animal level economic losses from PPR and vaccination cost, it can be conjectured that vaccination will pay if outbreaks of PPR in the district occur more often than once every 13 years, without considering the sizeable long-term and indirect benefits of PPR control. In conclusion, PPR causes high morbidity and mortality resulting in high economic loss, significantly reducing the income and livelihoods of sheep and goat producers, and other value chain actors. Vaccination reduces PPR impact in a cost-effective way and strengthening vaccination programs is likely to reduce economic impact and improve livelihoods.